2003
DOI: 10.1046/j.0931-2668.2003.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and QTL mapping for Sus scrofa chromosome 7

Abstract: Summary Linkage maps of Sus scrofa chromosome 7 (SSC7) for three informative F2 families, based on Wild Boar (W), Meishan (M) and Pietrain (P) crosses, were constructed using 16 marker loci. Maps were consistent for the families, except the order of the markers PI2‐PO1A‐S0212 in the W × M family which was inverted in the M × P and W × P families. Important quantitative trait loci (QTLs) were localized in the region of the SLA complex in the M × P and W × M families. These explained up to 16% of F2 phenotypic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
(34 reference statements)
5
17
1
Order By: Relevance
“…Among the 25 mapped SNPs, the largest number were on SSC1 (9), and the rest were distributed on SSC6 (6), SSC7 (3), SSC9 (2), SSC12 (2), SSC16 (2) and SSCX (1). The location of the SNPs on SSC1 and SSC7 were consistent previous reports [7,13], and the SNPs on SSC1 showed the greatest association with the trait. The top four significant SNPs were located on SSC1 (ALGA0006623, ALGA0006599, INRA0004898 and DRGA0001605).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Among the 25 mapped SNPs, the largest number were on SSC1 (9), and the rest were distributed on SSC6 (6), SSC7 (3), SSC9 (2), SSC12 (2), SSC16 (2) and SSCX (1). The location of the SNPs on SSC1 and SSC7 were consistent previous reports [7,13], and the SNPs on SSC1 showed the greatest association with the trait. The top four significant SNPs were located on SSC1 (ALGA0006623, ALGA0006599, INRA0004898 and DRGA0001605).…”
Section: Resultssupporting
confidence: 78%
“…gov/) functional annotation [7]. Two SNPs (H3GA00 20700 and MARC0069646) corresponded to a fat QTL region between TNFB (58 cM) and S0102 (70.1 cM) on SSC7 [13]. In Population 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The additive effect of the QTL was 0.21 cm, with the Large White allele increasing the LEW. Although several studies reported that there were significant QTL affecting LP and LEA around this region using different experimental animals (Sato et al, 2003;Yue et al, 2003;Sanchez et al, 2006;Uemoto et al, 2008), no QTL for LP and LEA with significant level were detected in the present study. This phenomenon might be due to the differences of experimental designs as well as statistical models.…”
Section: Sw2155contrasting
confidence: 45%
“…Meishan allele caused decrease in CW and DP, which was consistent with breed phenotype. As carcass weight can reflect an indirect measure of dressing percentage, several studies identified significant QTL for carcass weight on SSC7 (Andersson-Eklund et al, 1998;Sato et al, 2003;Yue et al, 2003). A significant QTL affecting carcass weight between TNFB and S0102 was found in …”
Section: Sw2155mentioning
confidence: 99%
“…M1 and M2 isoforms are encoded from the PKM (Pyruvate Kinase Muscle) gene (Noguchi, Inoue, and Tanaka, 1986) located in q12-q23 on porcine chromosome 7 (Davoli et al, 2002;Fontanesi et al, 2004), a region associated with highly reported to contain QTLs related to meat quality, fat deposition, and growth traits (Bidanel et al, 2001;Gilbert et al, 2007;Malek et al, 2001;Nezer et al, 2002;Ovilo et al, 2002;Reiner et al, 2002;Rohrer and Keele, 1998;Yue et al, 2003). PKM2 is a particularly promising positional candidate gene that plays a crucial role in porcine meat quality (Duan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%